Data structures, data abstraction a contemporary introduction using C++ - Model, Mitchell L. (Prentice Hall, 1994)
Multifaceted in its approach, this text provides a conceptual framework for thinking about, implementing and using data structures, offers a gentle introduction to C++ - with emphasis on data structures - and teaches a modern data abstraction style of programming. The book provides a complete introduction to C++, data abstraction and data abstraction programming in C++, teaching effective uses of C++ as a data abstraction language without getting into the complexities of inheritance and object-oriented programming, and offers a disciplined conceptual framework that reveals essential similarities among kinds of structures. The book organizes implementations around a set of fundamental operations common to all data structures and analyzes the organizational and functional characteristics of the different kinds of data structures. The text shows full implementation of every data structure discussed - sometimes with several variations, and the readable coding style emphasizes modern data abstraction approaches.